International Polar and Geophysical Years - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Det internasjonale polaråret (IPY); forskning; internasjonal samarbeid

Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Delivering 21st century Antarctic and Southern Ocean science - Kennicutt, Mahlon C I I; Kim, Yeadong; Rogan-Finnemore, Michelle; Anandakrishnan, Sridhar; Chown, Steven L; Colwell, Steven (Antarctic Science, 2016)
The Antarctic Roadmap Challenges (ARC) project identified critical requirements to deliver high priority Antarctic research in the 21st century. The ARC project addressed the challenges of enabling technologies, facilitating access, providing logistics and infrastructure, and capitalizing on international co-operation. Technological requirements include: i) innovative automated in situ observing systems, sensors and interoperable platforms (including power demands), ii) realistic and holistic numerical models, iii) enhanced remote sensing and sensors, iv) expanded sample collection and retrieval technologies, and v) greater cyber-infrastructure to process ‘big data’ collection, transmission and analyses while promoting data accessibility. These technologies must be widely available, performance and reliability must be improved and technologies used elsewhere must be applied to the Antarctic. Considerable Antarctic research is field-based, making access to vital geographical targets essential. Future research will require continent- and ocean-wide environmentally responsible access to coastal and interior Antarctica and the Southern Ocean. Year-round access is indispensable. The cost of future Antarctic science is great but there are opportunities for all to participate commensurate with national resources, expertise and interests. The scope of future Antarctic research will necessitate enhanced and inventive interdisciplinary and international collaborations. The full promise of Antarctic science will only be realized if nations act together.
Keywords: Antarktis; forskning; vitenskap

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Commercial fishing vessel as research vessels in the Antarctic – Requirements and solutions exemplified with a new vessel - Godø, Olav; Reiss, Christian; Siegel, V; Watkins, Jonathan (CCAMLR science journal of the Scientific Committee and the Commission for the Conservation of Antarctic Marine Living Resources, 2014)
Keywords: Antarktis; fiskefartøy; forskning; forskningsfartøy; klimaendringer; oseanografi; økosystem

Norge i Antarktis - Rognhaug, Magnus Hovind (red.) (Norsk Polarinstitutt, 2014)
Keywords: Antarktis; Antarktistraktaten; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Sørishavet; forskning; miljøvern; polarforskning; politikk

The friend who outstayed his welcome? Johan Hjort and the difficulties of bringing science to bear upon whaling - Roberts, Peder (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Sørishavet; fiskeripolitikk; forskning; hvalbestanden; hvalfangst; pelagisk

Cruising for krill in the Southern Ocean with G.O. Sars - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Institute of Marine Research, 2010)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

The Southern Ice Ocean Model Intercomparison Project (SIOMIP) - O'Farrell, Siobhan (Ice and climate news, 2007)
Keywords: Sørishavet; forskning; glasiologi; havis

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Antarctic sea ice processes and climate program, The International Polar Year - Ackley, Steve; Worby, Tony (Ice and climate news, 2006)
Keywords: Sørishavet; forskning; glasiologi; havis; klima

Polar-Noreg : det kvite eventyret - Elstad, Åsa; Balto, Ann Kristin (bildered.) (Universitetet i Tromsø, 2005)
Keywords: Antarktis; fangst; forskning; historie; oppdagelser; polarområdene; utstillinger

Polar Norway : the white adventure - Elstad, Åsa; Balto, Ann Kristin (bildered.) (Universitetet i Tromsø, 2005)
Keywords: Antarktis; fangst; forskning; historie; oppdagelser; polarområdene; utstillinger

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Å spise kirsebær med de store - Friedman, Robert Marc (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; Norsk Polarinstitutt; ekspedisjoner; forskning; oppdagelsesreiser

Klodens helse - sett fra polene - Hessen, Dag O (Norsk polarhistorie, 2004)
Keywords: Antarktis; Dronning Maud Land; Norge; ekspedisjoner; forskning; internasjonalt samarbeid

Antarctica - Sale, Richard (Polar reaches : the history of Arctic and Antarctic exploration, 2002)
Keywords: Antarktis; Sydpol; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; hvalfangere; oppdagelsesreiser; polarområdene

Research on Antarctic affairs at the FNI (Nansen news, 2001)
Keywords: Antarktis; forskning

IFIX - inductive data acquisition system: system for sub ice shelf data acquisition - Lothe, Torleif (Filchner-Ronne Ice Shelf Programme. Report, 2000)
Keywords: Antarktis; Sørishavet; forskning; teknologi

Strategi for norsk forskning i Antarktis - forskningsråd, Norges (Norges forskningsråd, 1997)
Keywords: Antarktis; Antarktistraktaten; Norge; forskning; forvaltningsansvar; miljøendringer; polarområdene

Belgica-ekspedisjonen : et hundreårsminne - Lie, Svein B (Norvegiana Nytt, 1997)
Keywords: Antarktis; Belgica ekspedisjon; forskning; oppdagelsesreiser; polarekspedisjoner

The final report of the Fridtjof Nansen Institute on the International Antarctic Regime Project (Fridtjof Nansens institutt, 1995)
Keywords: Antarktis; forskning

Subantarctic island research: discussion and recommendations - Sømme, Lauritz (Progress in conservation of the Subantarctic islands: proceedings of the SCAR/IUCN Workshop on Protection, Research and Management of Subantarctic Islands, Paimpont, France, 27-29 April 1992, 1995)
Keywords: Sørishavet; forskning; forvaltning; natur

Antarktis - den siste villmark - Lorentsen, Svein-Håkon (NINA-Nytt, 1994)
Keywords: Dronning Maud Land; ekspedisjoner; forskning

Digestibility of krill (Euphausia superba and Thysanoessa sp.) in minke whales (Balaenoptera acutorostrata) and crabeater seals (Lobodon carcinophagus) - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (British Journal of Nutrition, 1994)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Resource limitation in a long-lived seabird, the Antarctic petrel Thalassoica antarctica: a twining experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1993)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Norway in the Antarctic - Brekke, Annemor (Ministry of Foreign Affairs, 1993)
Keywords: Antarktis; Antarktistraktaten; Norge; ekspedisjoner; forskning; hvalfangst; miljø

The Norwegian-British-Swedish Antarctic expedition 1949-1952 - Liljequist, Gösta H (High latitudes : a history of Swedish polar travels and research, 1993)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Digestibility of krill in crabeater seals and minke whales - Mårtensson, Per-Erik; Nordøy, Erling S; Blix, Arnoldus Schytte (1993)
Keywords: Dronning Maud Land; forskning; hvaler; krill; plankton; seler; zoologi

Aspects of the breeding biology of the Antarctic Petrel Thalassoica antarctica and the krill requirement of the chicks, at Svarthamaren in Mühlig-Hofmanfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; krill; ornitologi; zoologi

Notes on the south polar skua Catharacta Maccormicki breeding at Svarthamaren in Mühlig-Hofmannfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The density of breeding and non-breeding Antarctic petrels at Svarthamaren, Dronning Maud Land, 1990 - Røv, Nils (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Vurdering av turisme i tilknytning til nordisk forskningsekspedisjon til Antarktis 1992/93 - Widmark, Eva Marie; Jørstad, Knut (Norsk Polarinstitutt, 1991)
Keywords: Antarktis; ekspedisjoner; forskning; turisme

Antarctic science in a historical perspective: changing roles and functional development - Indreeide, Thor Vidar (International Challenges, 1990)
Keywords: Antarktis; forskning; historie; vitenskap

SCAR in the ATS: conflict or harmony? - Rinaldi, Carlos (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning; politikk

Resource management and the changing profile of science in Antarctica: a growing pressure for relevance? - Scully, Richard Tucker (International Challenges, 1990)
Keywords: Antarktis; forskning; forvaltning

Forholdet mellom vitenskap og politikk i internasjonal ressursforvaltning: det internasjonale samarbeid om forvaltning av de levende marine ressurser i Antarktis - Indreeide, Thor Vidar (Fridtjof Nansens institutt, 1989)
Keywords: Antarktis; Sørishavet; forskning; forvaltning; politikk; ressurser

Size variation in the snow petrel Pagodroma nivea - Haftorn, Svein; Mehlum, Fridtjof; Bech, Claus (Notornis, 1988)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The South Pole expedition 1910-1912 - Huntford, Roland (The Amundsen photographs, 1987)
Keywords: Antarktis; Roald Amundsen; Sydpolen; Sydpolsekspedisjonen; ekspedisjoner; forskning; fotografihistorie; historie; oppdagelsesreiser; polarområdene

Antarktis petrellen - verdens mest hardføre fugl? - Haftorn, Svein (Viten : populær vitenskap, 1986)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Petreller i Dronning Maud Land - Mehlum, Fridtjof (Polarboken, 1986)
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Swedish Antarctic research. A historical Review - Liljequist, Gösta H (Sweden and Antarctica, 1985)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; meteorologi

Scientific research and cooperation in Antarctica - Gjelsvik, Tore (Antarctic challenge: conflicting interests, cooperation, environmental protection, economic development, 1984)
Keywords: Antarktis; forskning; forvaltning

The mineral resources of Antarctica: progress in their identification - Gjelsvik, Tore (Antarctic Resources Policy: Scientific, Legal and Political Issues, 1983)
The increment in informationCareful geological investigations started at a few places in Antarctica after World War II, but gained momentum and became systematic only when the International Geophysical Year started, and when SCAR and its Working Group on Geology were established just 25 years ago. Although geology was not initially part of the IGY programme, it soon became one of the thriving sciences in Antarctica.The growth of Antarctic geosciences can be shown in many ways, for example by the expansion of the Symposium volumes from the first one in 1963, containing 76 papers, to the latest one in August 1982, with 191 papers.The investigations have largely had the character of regional reconnaissance surveys, and the observations have mostly been published as general descriptions with maps at the scale of 1:1 million or smaller. Only one Antarctic nation has a systematic mapping programme of larger scales (1:500,000). In a few cases, such as in areas around some larger stations, more detailed work has been going on, in some cases also related to mineral occurrences. A few programmes are under way that have aspects of being resource-oriented: investigations of the Dufek Massif, a layered intrusion similar to the Cr-, Pt- and Ni-rich Bushfeld complex in South Africa, and sampling of manganese nodules during marine geological surveys. Airborne radiometric surveys and also some marine seismic surveys conducted by national oil companies or by resource-oriented state agencies belong to this category.
Keywords: Antarktis; ekspedisjoner; forskning; geologi; mineraler; ressurser

Automatic collection of tilt and strain data from tabular icebergs - Kristensen, Monica; Squire, Vernon A (Annals of Glaciology, 1983)
Keywords: Antarktis; forskning; glasiologi; isbreer

Insekter i Antarktis - Sømme, Lauritz (Forskningsnytt, 1983)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

Sommer i Antarktis: blant pingviner, sel og hvalfangstminner - Sømme, Lauritz (Universitetsforlaget, 1983)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; natur; økologi

The Southern giant petrel Macronectes giganteus (Gmelin) on Bouvet Island - Haftorn, Svein; Voisin, Jean-Francois (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1982)
Keywords: Bouvetøya; forskning; fugler; ornitologi; zoologi

Present-day glaciation in the South Shetland Islands - Orheim, Olav; Govorukha, Leonid Sergeevich (Annals of Glaciology, 1982)
Keywords: Antarktis; firnsnø; forskning; glasiologi; isbreer; stratigrafi; vulkaner

Iceberg response to sea state - Orheim, Olav; Wadhams, Peter; Kristensen, Monica (Iceberg research, 1982)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; isberg; isfjell; målinger

The geology, volcanic activity, and age of Bouvetøya, South Atlantic - Prestvik, Tore (Norwegian Antarctic Research Expeditions (1978/79), 1982)
Keywords: Bouvetøya; ekspedisjoner; forskning; geologi; vulkaner

Adaptation to low temperature in Antarctic terrestrial arthropods - Sømme, Lauritz (Comite National Francais Des Recherches Antarctiques, 1982)
Keywords: Antarktis; ekspedisjoner; forskning; kuldetoleranse; virvelløse dyr

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Studies of icebergs, ice fronts and ice walls using side-scanning sonar - Klepsvik, John O; Fossum, Bjørn A (Annals of Glaciology, 1980)
Keywords: Dronning Maud Land; NARE 1978/79; ekspedisjoner; forskning; glasiologi; is; isberg; isfjell; isfront; morfologi; snø

Ice-shelf underwater morphology - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: Antarktis; NARE 1976/77; ekspedisjoner; forskning; glasiologi; isshelf; morfologi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Verdens kaldeste sjøvann - Foldvik, Arne; Gade, Herman G (Naturen, 1978)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; observasjoner; oseanografi; sjøvann; vannmasser

Basaltene i Vestfjella og Gondwanalands historie - Furnes, Harald (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geokjemi; geologi; petrologi

Cryptopygus sverdrupi n.sp. A new species of Collembola (Isotomidae) from Sverdrupfjella, Antarctica, with notes on related species in five genera - Lawrence, Peter N (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; leddyr

Hva den fossile magnetiseringen i Vestfjella kan fortelle - Løvlie, Reidar (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geologi; jordmagnetisme

Insektliv i Antarktis - Sømme, Lauritz (Naturen, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; insekter; zoologi

Kuldetoleranse hos alpine og arktiske collemboler - Sømme, Lauritz (Entomologisk tidskrift, 1978)
Keywords: Antarktis; ekspedisjoner; entomologi; forskning; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Notes on the cold-hardiness of prostigmate mites from Vestfjella, Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; kuldetoleranse; midder; miter; virvelløse dyr; zoologi

The entomology of Antarctica, with special reference to Dronning Maud Land - Sømme, Lauritz (Norwegian Journal of Entomology, 1978)
Keywords: Dronning Maud Land; ekspedisjoner; entomologi; forskning; leddyr; zoologi

Hvor driver de antarktiske isfjellene? - Vinje, Torgny E (Naturen, 1978)
Keywords: Sørishavet; Weddellhavet; drivis; forskning; havis; havstrømmer; isberg; isdrift; issfjell; oseanografi; sjøis; sjøvann

Back to the Antarctic - Orheim, Olav (Research in Norway, 1977)
Keywords: Bouvetøya; forskning; marinbiologi

Prostigmate mites (Acari, Prostigmata) from Sverdrupfjella, Dronning Maud Land, with description of four new species - Strandtmann, Russell W; Sømme, Lauritz (Norwegian Journal of Entomology, 1977)
Keywords: Dronning Maud Land; ekspedisjoner; forskning; midder; miter; virvelløse dyr; zoologi

Hva gjør Norge i Antarktis? - Orheim, Olav (Norske interesser i polarområdene, 1976)
Keywords: Antarktis; ekspedisjoner; forskning; politikk

Past and present mass balance variations and climate at Deception Island, South Shetland Islands, Antarctica - Orheim, Olav (International Association of Hydrological Sciences, 1975)
Keywords: Antarktis; forskning; glasiologi; klimatologi

A forgotten explorer: Carsten Egeberg Borchgrevink - Evans, Hugh B; Jones, A G E (Polar Record, 1974)
Keywords: Antarktis; biografi; ekspedisjoner; forskning; oppdagelsesreiser

Vitenskapelig utforskning som internasjonalt samarbeidsprosjekt i polarområdene - Skagestad, Odd Gunnar (Stiftelsen, 1974)
Keywords: Antarktis; forskning; jus; politikk

Antarctic resources: report form the informal meeting of experts 30 May - 9 June 1973 (Fridtjof Nansen-stiftelsen på Polhøgda, 1973)
Keywords: Antarktis; forskning; jus; politikk; ressurser

Sydpolisen opptil 4000 m tykk: Sydpollandet har 95 pst. av isen i verden! - Lund, Thoralv (Polarposten, 1971)
Keywords: Antarktis; forskning

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Biology and population dynamics of Antarctic seals - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: Sørishavet; biologi; forskning; marinbiologi; seler; zoologi

Norwegian pelagic sealing reconnaissance in the Scotia Sea, 1964 - Øritsland, Torger (Polar Record, 1970)
Keywords: Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Sealing and seal research in the south-west Atlantic pack ice, Sept.-Oct. 1964 - Øritsland, Torger (Antarctic ecology, 1970)
Keywords: MV Polarhav; Sørishavet; biologi; ekspedisjoner; forskning; marinbiologi; seler; zoologi

Amerikanske kvinnelige vitenskapsmenn studerer pingviner i Antarktis - Schroth, Charles (Polarposten, 1969)
Keywords: Antarktis; forskning

Antarktistraktaten, territorialkravene, forskningssamarbeidet - Bolin, Fredrik Th. (Polarboken, 1968)
Keywords: Antarktis; forskning; jus; politikk

Ascidians collected during 1928-1930 by the Norwegian Antarctic expeditions - Millar, Robert Hannay (Universitetsforlaget, 1968)
Keywords: Antarktis; dyr; ekspedisjoner; forskning; kappedyr; tunicata; zoologi

En del sovjetiske forskningsinstitusjoner, med særlig vekt på de som arbeider med oppgaver i arktiske og antarktiske strøk - Heintz, Natascha ([Norsk Polarinstitutt], 1965)
Keywords: Antarktis; forskning; polarområdene; vitenskap

Christensen and Mawson - Grierson, John (Challenge to the poles : highlights of Arctic and Antarctic aviation, 1964)
Keywords: Antarktis; Hjalmar Riiser; Lars Christensen; Larsen; Norvegia ekspedisjoner; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; luftfart; oppdagelsesreiser

The Norwegian/British/Swedish Expedition to Queen Maud Land - Grierson, John (Challenge to the poles : highlights of Arctic and Antarctic aviation, 1964)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; luftfart

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

Lys over "tåkeheimen" i sør: den videnskapelige serie fra Lars Christensens ekspedisjoner avlsuttet - Isachsen, Fridtjov (Norsk hvalfangst-tidende, 1962)
Keywords: Antarktis; Sørishavet; forskning; litteratur; naturvitenskap; vitenskap

The Winning of Australian Antarctica: Mawson's BANZARE voyages, 1929-31, based on the Mawson Papers - Price, Archibald Grenfell (ed.) (Angus and Robertson, 1962)
Keywords: Antarktis; Lars Christensen; Norvegia ekspedisjoner; Sydpolen; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; oppdagelsesreiser

Man in Antarctica - Rodahl, Kaare (Science in Antarctica. Part 1: The Life sciences in Antarctica, 1961)
Keywords: Antarktis; ekspedisjoner; forskning; fysiologi; kuldetoleranse; medisin; polarområdene

Norwegian air photography in Dronning Maud Land: Operation “Pingvin”, 1958–59 - Luncke, Bernhard (Polar Record, 1960)
Keywords: Dronning Maud Land; ekspedisjoner; flyfoto; flyfotografering; forskning; luftfoto; topografi

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

U južnogo poljusa god 1900 - Borchgrevink, Carsten Egeberg (1958)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Modchejm : Dva goda v Antarktike. Nauchnaia Norvezhsko-Britansko-Shvedskaia ekspeditsiia 1949-1952 - Giæver, John Schjelderup; Sokolovoj, A V (Gosudarstvennoe Izdat. Geograficheskoi Literatury, 1958)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Twee jaar in het zuidpool-gebied met de Maudheim-expeditie : de spannende ervaringen van de Noors-Brits-Zweedse expeditie van 1949-1952 naar Antarctis - Giæver, John Schjelderup; Baars, Herman D; Visser, N G; Baars-Jelgersma, Greta (W. de Haan, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Bijela pustinja : dvije godine u Antarktiku : norvesko-britansko-svedska istrazivacka ekspedicija u Antarktiku 1949-1952 - Giæver, John Schjelderup; Mardešić, Petar (Kultura, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Station im Eis : zwei Jahre in der Antarktis : die Norwegisch-Britisch-Schwedische wissenschaftliche Antarktisexpedition 1949-1952 - Giæver, John Schjelderup; Reiher, H (Hermann Haack, 1956)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Narrative of the Expedition - Larsen, Nils (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

The Norwegian Antarctic expedition in the "Brategg 1947-1948 - Mosby, Håkon (Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48, 1956)
Keywords: Brategg ekspedisjon; Peter I. Øy; Sørishavet; ekspedisjoner; forskning; naturvitenskap; oseanografi; zoologi

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Asahi Shimbun Sha, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Chatto & Windus, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

Maudheim : deux ans dans l'Antarctique : l'expedition scientifique norvégienne, britannique et suédoise dans l'Antarctique en 1949-1952 - Giæver, John Schjelderup; Poterat, Jacques (Denoël, 1954)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Antarktis : norjalais-brittiläis-ruotsalaisen tieteellisen Antarktisretkikunnan vaiheet - Giæver, John Schjelderup; Kilpeläinen, Matti (WSOY, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Queen Maud Land Expedition - Robin, Gordon de Quetteville (Marine Observer, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Physiological changes in blood in the Antarctic. A preliminary report - Wilson, Ove (British Medical Journal, 1953)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskning; fysiologi; medisin; observasjoner

Soldage og polarnætter : Norselekspeditionen til Antarktis 1949-1952 - Giæver, John Schjelderup; Windfeld-Hansen, Karina (Grafisk Forlag, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Antarktisboken : med Norsel till Maudheim och Antarktis : den norsk-brittisk-svenska vetenskapliga expeditionen till Antarktis 1949-1952 - Giæver, John; Schytt, Valter (Forum, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Den norsk-brittisk-svenska antarktisexpeditionen 1949-52. Kort översikt av det andra årets arbeten - Liljequist, Gösta H; Schytt, Valter (Ymer, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Fishes collected during the Norwegian-British-Swedish Antarctic expedition 1949-52 - Nybelin, Orvar (1952)
Keywords: Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; Sørishavet; fisker; forskning; zoologi

Queen Maud Land. The Scientific Results of the International Expedition - Robin, Gordon de Quetteville (Geographical Magazine, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Antarctic Bryozoa - Vigeland, Immanuel (Dybwad, 1952)
Keywords: Antarktis; bløtdyr; bryozoa; ekspedisjoner; forskning; mosdyr; zoologi

Life at Maudheim - Robin, Gordon de Quetteville (Geographical Magazine, 1951)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

An international expedition to Antarctica. The Voyage to Queen Maud Land - Roots, Ernest Frederick (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi

An international expedition to Antarctica - Kirwan, Laurence Patrick (Geographical Magazine, 1949)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning

Den planerade norsk-svensk-brittiska Antarktis-expeditionen - Ahlmann, Hans Wilhelmsson (Ymer, 1948)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi; glasiologi; meteorologi

"Brategg"-ekspedisjonen 1947-48 = The "Brategg" expedition 1947-48 (Norsk hvalfangst-tidende, 1947)
Keywords: Sørishavet; ekspedisjoner; forskning

Antarctic fishes - Nybelin, Orvar (Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq. Instituted and financed by consul Lars Christensen : Volume II, 1947)
Keywords: Sørishavet; ekspedisjoner; fisker; forskning; zoologi

The Falkland Islands Dependencies Survey, 1943-46 - Wordie, James Mann (Norsk hvalfangst-tidende, 1947)
Keywords: Antarktis; Sørishavet; ekspedisjoner; forskning; kartlegging; logistikk

Lars Christensen-ekspedisjonenes videnskapelige resultater - Holtedahl, Olaf (Polar-årboken, 1945)
Keywords: Antarktis; ekspedisjoner; forskning

Vår ishavsflåte og selfangsten : ishavsskutenes innsats i arktisk og antarktisk forskning - Hansen, Rolf (Vår Flåte, 1944)
Keywords: Sørishavet; ekspedisjoner; forskning; polarområdene; selfangst

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

Norwegians in the Antarctic - Aagaard, Bjarne (The American-Scandinavian Review, 1934)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

On vertical circulation in the ocean due to the action of the wind with application to conditions within the Antarctic circumpolar current - Sverdrup, Harald Ulrik (Discovery Reports, 1933)
Keywords: Sørishavet; ekspedisjoner; forskning; havstrømmer; oseanografi

Polaraaret 1932-1933 (Norsk hvalfangst-tidende, 1932)
Keywords: Sørishavet; forskning; klima; meteorologi; oseanografi

The work of the whalers and the discovery committee - Hayes, Gordon J (The conquest of the South Pole : antarctic exploration 1906-1931, 1932)
Keywords: Antarktis; Carl Anton Larsen; Lars Christensen; Odd I; ekspedisjonen; ekspedisjoner; forskning; hvalfangere; hvalfangst; oppdagelsesreiser; polarområdene

Whaling and Exploring in the Antarctic - Aagaard, Bjarne (Norwegian Trade Review, 1929)
Keywords: Lars Christensen; Norvegia ekspedisjonene; Sørishavet; ekspedisjoner; forskning; geografi; hvalfangere; hvalfangst; pelagisk; polarområdene

Litt om "Norveiga"-ekspedisjonen 1927-28 og dens arbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1929)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; forskning; geografi; marinbiologi; oseanografi

Die Bouvet-Insel : Inaugural-Dissertation der Philosophischen Fakultät der universität Leipzig zur Erlangung der Doktorwürde - Engelmann, Gerhard (s.n., 1923)
Keywords: Bouvetøya; forskning; historie; oppdagelsesreiser

Sydpol-forskning : en utsigt over dens utvikling gjennem tiderne - Skattum, Ole Jacob (I kommission hos Aschehoug, 1912)
Keywords: Antarktis; Sydpolen; ekspedisjoner; forskning; oppdagelsesreiser

Das Festland am Sydpol : die Expedititon zum Sydpolarland in den Jahren 1898-1900 - Borchgrevink, Carsten Egeberg (Schottlaender, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Magnetic and meteorological observations made by the "Southern Cross" Antarctic expedition 1898-1900 - Borchgrevink, Carsten Egeberg; Bernacchi, Louis (Royal Society of London, 1902)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; magnetisme; meteorologi; observasjoner; oppdagelsesreiser; polarekspedisjoner

To the South Polar regions : expedition of 1898-1900 - Bernacchi, Louis Charles (Bluntisham Books, 1901)
Keywords: Antarktis; Southern Cross; astronomi; biografi; ekspedisjonen; ekspedisjoner; forskning; fysikk; geologi; klimatologi; oppdagelsesreiser; overvintring; zoologi

Den antarctiske expedition. Foredrag den 18de mai 1898 - Borchgrevink, Carsten Egeberg (Det Norske geografiske selskabs aarbok, 1898)
Keywords: Antarktis; Southern Cross (skip); forskning; oppdagelsesreiser; polarekspedisjoner; vitenskapelige ekspedisjoner

Antarctic exploration - Borchgrevink, Carsten Egeberg (Strand Magazine, 1897)
Keywords: Antarktis; Southern Cross; ekspedisjonen; ekspedisjoner; forskning; geografi; oppdagelsesreiser; overvintring

Den sidste antarctiske reise og foreløbig plan for en ny expedition. Foredrag den 30te oktober 1895 - Borchgrevink, Carsten Egeberg; Bull, Henrik Johan (Det Norske geografiske selskabs aarbok, 1896)
Keywords: Antarktis; Kapp Adare; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner

Norway's Antarctic research activities: report to SCAR - Norsk Polarinstitutt; Polarinstitutt, Norsk (Norwegian Polar Institute)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; forskning; forvaltning